THE EXPERIENCES OF LAY COUNSELLORS REGARDING HIV AND AIDS CARE AND SUPPORT IN TSHWANE CLINICS - Mkhabele, Chuene; Peu, Doriccah (Southern African Journal of Social Work and Social Development, 2016)
Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) is a major burden disease in South Africa. The pandemic characterises the need for increased counselling and testing due to the availability of antiretroviral therapy (ART). This study describes the experiences of lay counsellors regarding care and support for HIV and AIDS. A qualitative approach was used during focus group interviews at four Tshwane clinics. The purposive sampling method was used to select participants from each facility. Data were collected and data analysis conducted using Tesch’s method. The results highlight that lay counsellors are not recognised as part of the health workers and multidisciplinary team by the Department of Health. It was recommended that the lay counsellors be retained as stipend earning government workers with clearly stipulated and revised conditions of service. On-going support, managerial support and supervision are necessary to improve care and support of HIV and AIDS.